The Implementation of the Balanced Scorecard for Improving Quality of Education - Agoes Dariyo; Sanusi Uwes; Raja Oloan Tumanggor (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The Balanced Score-Card is a principle of managing professional and balanced organizational institutions concerning financial and non-financial aspects. The BSC can be applied to for-profit and non-profit institutions, such as the Putra Satria educational institution. This study uses a qualitative-descriptive approach. It is collecting data by interview, observation, and documentation notes. Data analysis refers to the balanced scorecard theory, which includes financial and non-financial aspects. The result is that the BSC has been implemented well by the Putra Satria Junior High School so that the school has a financial surplus. In addition, internal and external customers aspects of customer satisfaction feel satisfied with school management services. Internal business aspects by carrying out innovations in facilities and infrastructure that have been carried out by school management, as well as innovations in teaching (teaching and learning activities), carried out by teachers. In addition, it was found that the school cares for the development of human resources for teachers and employees through courses, training, seminars, or academic activities that support improving their education.